ANÁLISIS Y EVALUACIÓN ECONÓMICA FINANCIERA A LA COOPERATIVA DE AHORRO Y CRÉDITO INTI WASI LTDA. INTI COOP DE LA CIUDAD DE SARAGURO, PERIODO 2013-2014 - Ordóñez Ureña, María Stefanya (2016)
This thesis entitled " Financial Analysis and Economic Assessment Panel to the credit union Inti Wasi INTI Ltda COOP Saraguro City , 2013-2014 . " ; allowed to know the economic and financial position of the cooperative through the analysis and evaluation of data presented in the financial statements ; its importance is that it allows to be aware of the levels of profitability , risk, competitiveness and sustainability of activities over time; to determine the effectiveness of financial management , the success of the cooperative and the maximization of value for the shareholders. The development work was based on the fulfillment of the overall objective to analyze and assess economic and financial support to the credit union Inti Wasi Ltda. Saraguro city during the period 2013-2014. Similarly, the fulfillment of specific objectives was necessary: Apply and interpret financial indicators of solvency, profitability, indebtedness, activity, and the governing body established by the regulator, which determined the economic and financial situation of the cooperative and were compared standards issued by regulators. It's that same Assess the financial structure, working capital, cash conversion cycle and equilibrium point and financial risk, to diagnose the financial position of the cooperative and its economic and financial performance measure. Finally Prepare the final report and argue easily understood by managers and directors in which they presented the results of the analysis and economic evaluation and financial situation of the cooperative.